Real Time Design of Wireless Sensor Network for Monitoring ionized Radiation using Raspberry Pi (University of Khartoum Engineering Journal, 2021)
Early detection of ionized radiation using intelligent technology will minimize the number of casualties when radiation disasters occur. The objective of this paper is to design  sensors network using Raspberry pi technology able to detect any leakage of radiation. The design used the internet of things (IoT) to provide easy and safe monitoring in everywhere. This design calculates the radiation quantity in real time and provides both sound and LED alerts. Geiger-Mueller (GM) counter was used for sensing the ionizing radiation such as gamma rays. An application web was designed to ensure the facility of monitoring radiation everywhere. A daily report of radiation amount over the day can be obtained easily. Each radiation power level was represented by a set of LEDs with different colours. The structures contain sub-nodes, main node and raspberry pi node. XBEE used to connect between sub-nodes and the main node then Ethernet module is used to connect the main node to raspberry pi unit.